STUDENTS’ PERCEPTIONS OF WAYGROUND AI IN GAME-BASED LEARNING FOR ENHANCING ENGLISH VOCABULARY AT MAN PURWOREJO - Lyra Sandra Mulia; Juita Triana; Zulia Chasanah (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2026)
The game-based learning tools have been widely used in educational settings. Limited research has examined students’ perceptions of AI-powered game-based learning platforms. This study aimed to investigate students’ perceptions of the use of Wayground AI in game-based learning for enhancing English vocabulary at MAN Purworejo, an Islamic senior high school in Indonesia. A descriptive quantitative survey design was employed involving 25 students selected through purposive sampling, after which data were collected using a 20-item questionnaire based on the Technology Acceptance Model (TAM), covering perceived ease of use, perceived usefulness, attitude toward use, behavioral intention, and learning engagement. The data were analyzed using descriptive statistics, particularly mean scores. The findings revealed generally neutral-to-positive perceptions toward the use of Wayground AI. Among the five constructs, only attitude toward use showed a positive perception (M = 3.51), indicating that students generally enjoyed learning with the platform. Meanwhile, perceived ease of use (M = 3.39), perceived usefulness (M = 3.18), behavioral intention (M = 2.90), and learning engagement (M = 3.29) remained within the neutral category. Item-level analysis showed relatively higher ratings for enjoyment and interest in learning activities, whereas vocabulary retention and intentions for regular future use received lower scores. These findings suggest that Wayground AI can contribute to positive learning experiences and classroom participation. However, its perceived effectiveness for long-term vocabulary retention and sustained independent use remains limited. The study highlights the importance of integrating AI-supported game-based learning with consistent instructional support and follow-up activities to maximize its educational potential.